2010
DOI: 10.1007/s11427-010-0088-2
|View full text |Cite
|
Sign up to set email alerts
|

Integration mechanisms of transgenes and population fitness of GH transgenic fish

Abstract: It has been more than 20 years since the first batch of transgenic fish was produced. Five stable germ-line transmitted growth hormone (GH) transgenic fish lines have been generated. This paper reviews the mechanisms of integration and gene targeting of the transgene, as well as the viability, reproduction and transgenic approaches for the reproductive containment of GH-transgenic fish. Further, we propose that it should be necessary to do the following studies, in particularly, of the breeding of transgenic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 77 publications
1
15
0
5
Order By: Relevance
“…Our real-time PCR results showed that there were three exogenous GH genes in the hemizygous transgenic common carp genome. Based on further analysis of the flanking sequences at the integration site, we confirmed that the copy number of the hemizygous transgenic common carp was in fact just two, which supports the hypothesis that high expression is associated with low copy number [3].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our real-time PCR results showed that there were three exogenous GH genes in the hemizygous transgenic common carp genome. Based on further analysis of the flanking sequences at the integration site, we confirmed that the copy number of the hemizygous transgenic common carp was in fact just two, which supports the hypothesis that high expression is associated with low copy number [3].…”
Section: Discussionsupporting
confidence: 75%
“…Compared with distant hybridization, transgenic techniques show greater perspective in animal breed improvement because of its illimitation in species and desired traits [1], although the potential ecological risk of transgene needs to be hedged by some measures such as reproduction control [2][3][4]. The development of fish breeding and aquaculture will accelerate once the genes associated with economically important traits in fishes are discovered and introduced into target species by transgenic techniques [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this century, the cloned zebrafish were obtained by nuclear transfer from long-term-cultured cells [35], and the cytoplasmic impact was analyzed in cross-genus cloned fish derived from transgenic common carp (Cyprinus carpio) nuclei and goldfish (Carassius auratus) enucleated eggs [36]. Moreover, some differentially expressed genes were identified from the cloned zebrafish embryos at the dome stage [37], and the critical developmental stages for high integration efficiency were determined in zebrafish [38,39]. Stem cell culture and application have been rapidly developed in model fishes of medaka and zebrafish [40,41], and some stem cell technologies, such as gene targeting, germ cell transplantation and semi-cloning by nuclear transfer, have been successfully formed because of specific potentials of fish germ stem cells and embryonic stem cells [42,43].…”
Section: Somatic Cell Nuclear Transfer and Stem Cell Technologies In mentioning
confidence: 99%
“…The laboratory of Zhu ZuoYan has made outstanding contributions in this area [102,103]. To minimize the shortcomings of artificially induced triploid fish and control potential risks posed by transgenic fish introduction, the Institute of Hydrobiology of the Chinese Academy of Sciences has joined with Hunan Normal University to carry out hybridization experiments between Cyprinus carpio and 4nAT; a transgenic triploid fish showing fast growth, efficient feed conversion, and good breeding traits has been developed via hybridization of fish with differing ploidy levels [104].…”
Section: Application Of Fish Distant Hybridization Lineagesmentioning
confidence: 99%